2017
DOI: 10.1080/19491034.2016.1276143
|View full text |Cite
|
Sign up to set email alerts
|

Guard the guardian: A CRL4 ligase stands watch over histone production

Abstract: Histones are evolutionarily conserved proteins that together with DNA constitute eukaryotic chromatin in a defined stoichiometry. Core histones are dynamic scaffolding proteins that undergo a myriad of post-translational modifications, which selectively engage chromosome condensation, replication, transcription and DNA damage repair. Cullin4-RING ubiquitin E3 ligases are known to hold pivotal roles in a wide spectrum of chromatin biology ranging from chromatin remodeling and transcriptional repression, to sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The idea that CRL4 ligases are genome caretakers due to their prominent role during DNA replication and repair is not new (Lampert et al, 2017). In Arabidopsis, similar to the case of other organisms, this surveying function can be extended to other mechanisms directly related with DNA transcription.…”
Section: General Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The idea that CRL4 ligases are genome caretakers due to their prominent role during DNA replication and repair is not new (Lampert et al, 2017). In Arabidopsis, similar to the case of other organisms, this surveying function can be extended to other mechanisms directly related with DNA transcription.…”
Section: General Conclusion and Future Perspectivesmentioning
confidence: 99%
“…For example, ribonucleoprotein hnRNP H/F plays a key role in binding to Gquadruplex structure in TP53 mRNA maintaining 3 0 end processing during global CpA inhibition (Decorsière et al, 2011). Additionally, the stem-loop structure formed by histone pre-mRNAs is recognized by stem-loop binding protein (SLBP) and is necessary for the 3 0 end processing of histone mRNAs (Battle & Doudna, 2001;Dominski & Marzluff, 1999;Lampert, Brodersen, & Peter, 2017;Marzluff & Koreski, 2017). More recent research has uncovered that the ubiquitin ligase CRL4, a protein complex notable for its role in genome stability (Abbas & Dutta, 2011) and UV-mediated proteolysis of cell cycle regulator p21 (Abbas et al, 2008), also monoubiquitinates SLBP, permitting proper histone mRNA 3 0 end maturation (Brodersen et al, 2016;Lampert et al, 2017).…”
Section: Competition Between Rbps and Mirnas In Controlling Gene Exmentioning
confidence: 99%
“…Additionally, the stem-loop structure formed by histone pre-mRNAs is recognized by stem-loop binding protein (SLBP) and is necessary for the 3 0 end processing of histone mRNAs (Battle & Doudna, 2001;Dominski & Marzluff, 1999;Lampert, Brodersen, & Peter, 2017;Marzluff & Koreski, 2017). More recent research has uncovered that the ubiquitin ligase CRL4, a protein complex notable for its role in genome stability (Abbas & Dutta, 2011) and UV-mediated proteolysis of cell cycle regulator p21 (Abbas et al, 2008), also monoubiquitinates SLBP, permitting proper histone mRNA 3 0 end maturation (Brodersen et al, 2016;Lampert et al, 2017). During G2 stress, cyclin-F, the substrate recognition subunit of the Skp1-Cul1-F-box E3 ligase complex, targets SLBP to proteasomal degradation and limits H2A.X signaling and apoptosis following DNA damage (Dankert et al, 2016).…”
Section: Competition Between Rbps and Mirnas In Controlling Gene Exmentioning
confidence: 99%
“…Loss of CUL-4 could affect localization or function in a number of different proteins important for DSB formation. Another possibility is that DSB formation defects stem from CUL-4’s effect on chromosomal structure, since CUL-4 is known to ubiquitinate histones in humans and mice (discussed in: [85]). Our analysis also demonstrated that dysfunctional CRL4 can interfere with the repression of the Tc3 transposase.…”
Section: Discussionmentioning
confidence: 99%